KONTRIBUSI PEMAHAMAN KOSAKATA BIDANG JURNALISTIK TERHADAP KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS VIII SMP NEGERI 22 PADANG - Yonafri, Cindy; Emidar, Emidar (Universitas Negeri Padang, 2019)
ABSTRACT There are three objectives of this research. First, describing the comprehension of journalistic vocabulary at students grade VIII SMP Negeri 22 Padang. Second, describing the writing skill of news text at student grade VIII SMP Negeri 22 Padang. Third, describing the contribution of journalistic vocabulary towards the skill in writing news text at students grade VIII SMP Negeri 22 Padang. This is a quantitative research with descriptive method and using correlational research design. Population and sample of this research are VIII th grade student of SMP Negeri 22 Padang consist of 223 students and 44 sample students. This research use Simple Random Sampling technique. This experiment consists of two variables: vocabulary as the independent variable (X) and the writing skills of news text as a dependent variable (Y). Based of result data analyze and explanation, were concluded 3 case. First, comprehension of journalistic vocabulary on students grade at VIII SMP Negeri 22 Padang was on good qualification (83,88). Second, writing skills of news text at students grade VIII SMP Negeri 22 Padang was on good qualification (81,91). Third, comprehension vocabulary on environment areacontributed toward writing skills news text at students grade VIII SMP Negeri 22 Padang. Nevertheless, for the writing skills news text were needed comprehension of vocabulary on journalistic. Kata kunci : Kontribusi, Penguasaan Kosakata Bidang Jurnalistik, Keterampilan Menulis Teks Berita